2019
DOI: 10.1111/dom.13702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colchicine in adults with metabolic syndrome: A pilot randomized controlled trial

Abstract: Aim To evaluate the efficacy and safety of colchicine for improving metabolic and inflammatory outcomes in people with obesity and metabolic syndrome (MetS). Materials and methods Adults with obesity and MetS, but who did not have diabetes, were randomized to colchicine 0.6 mg or placebo capsules twice daily for 3 months. The primary outcome was change in insulin sensitivity (SI) as estimated by insulin‐modified frequently sampled intravenous glucose tolerance tests. Secondary outcomes included changes in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 53 publications
3
42
1
Order By: Relevance
“…45 Finally, colchicine has also been shown to dampen the inflammatory response and reduce CRP levels among subjects with metabolic syndrome. 68 These data support the general anti-inflammatory effect of colchicine, independent of a specific disease state.…”
Section: Colchicine In Non-rheumatological Inflammatory Conditionssupporting
confidence: 59%
“…45 Finally, colchicine has also been shown to dampen the inflammatory response and reduce CRP levels among subjects with metabolic syndrome. 68 These data support the general anti-inflammatory effect of colchicine, independent of a specific disease state.…”
Section: Colchicine In Non-rheumatological Inflammatory Conditionssupporting
confidence: 59%
“…Although absolute reduction of hs-CRP and IL-6 were larger in these studies in which baseline levels were higher, the relative reduction was similar. The reduction in the current study was achieved with a lower dose of colchicine [21,22]. Systemic hs-CRP and IL-6 reduction have not been observed when administrating colchicine directly after acute myocardial infarction [14,23,24].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 51%
“…Pooled data from these studies showed 0.6% (95% CI 0.3, 0.9) of participants using colchicine reported a haematology event compared to 0.4% (95% CI 0.2, 0.7) of participants in placebo groups. The occurrence of haematology events in colchicine or comparator groups was reported by three studies [21,23,37]. The meta-analysis showed an overall non-significant RR (95% CI) of haematology events in 1.34 (0.64, 2.82) (Supplementary Figure 6, Table 2).…”
Section: Haematology Eventsmentioning
confidence: 97%
“…Characteristics of participants in the included studies are shown in Table 1. A number of disease states were studied including cirrhosis (n = 5 studies) [6][7][8][9][10], pericarditis (n = 4 studies) [26,27,29,31], gout (n = 5 studies) [15,18,34,38,39], knee osteoarthritis (n = 3 studies) [16,20,30], Behcet's syndrome (n = 3 studies) [21,32,40], psoriatic arthritis (n = 2 studies) [13,36], post-pericardiotomy syndrome (n = 2 studies) [25,28], chronic obstructive pulmonary disorder (n = 1 study) [19], bare-metal stent restenosis (n = 1 study) [22], metabolic syndrome (n = 1 study) [23], lung resection surgery (n = 1 study) [17], myocardial infarction (n = 1 study) [37], familial Mediterranean fever (n = 1 study) [12], asthma (n = 1 study) [24], primary sclerosing cholangitis (n = 1 study) [11], aphthous stomatitis (n = 1 study) [33], allergic rhinitis (n = 1 study) [14] and low back pain (n = 1 study) [35]. Sample sizes ranged from 11 to 4745, with a pooled sample of 8659 adult participants.…”
Section: Participant Characteristicsmentioning
confidence: 99%